Wireless power transmission and its annexure to the grid system - Ahmed, S. S. (IEEE, 2003)
Transmission or distribution of 50 or 60 Hz electrical energy from the generation point to the consumers’ end without any physical wire has yet to mature as a familiar and viable technology. Apart from a few demonstrations or feasibility studies the research effort thus far on wireless power transmission (WPT) is inadequate. Moreover, the reported works have not disclosed any design methodology. and this has restricted further advancement in the research on WPT. A unified,consistent and coherent mathematical model for WPT has been synthesised. The output obtained from the model when applied to a case has been compared against the technical specifications partially reported in the literature by a feasibility study of the same case. In addition, it is shown that a potential application of WPT would be in annexing a grid system for radial feed to a demand site in certain scenarios. Also. the specific aspects upon which further research should focus have heen identified so that WPT annexure can he viable in the discussed scenarios. The findings are expected to renew interest in WPT among the public in general and among the researchers and the environmentalists in particular.